Adding a Visual Communication Tool to the Electronic Health Record to Prevent Pressure Injuries. (1st March 2021) - Bouyer-Ferullo, Sharon; O'Connor, Charlene; Kinnealey, Ellen; Wrigley, Pamela; Osgood, Patrice M.
ABSTRACT: Health care organizations no longer receive reimbursement for stage 3, stage 4, and unstageable hospital‐acquired pressure injuries, which are never events that require interdisciplinary collaboration to treat and prevent. Perioperative patients are at risk for developing pressure injuries that may not manifest until five or more days after surgery. This quality improvement project aimed to inform inpatient nursing and health care professionals of the potential areas of skin breakdown after surgery using an annotated image (AI) depicting intraoperative patient positioning. To gauge OR nurses' use of the AI, we tracked image addition to the patient records weekly from May 2018 to May 2019 and found an overall average participation rate of 80% to 90%. Adding the AI of surgical positioning and pressure points raised awareness of the potential for skin breakdown and became a valuable communication tool for the inpatient nurses who were providing postoperative care to prevent pressure injuries.